PRECISE CRITERIA NEEDED IN EVALUATING ACCOUNTING ALTERNATIVES. - Young, Kenneth G. (The Accounting Review, 1957)
The article discusses the need for development of objective and explicit criteria for selecting proper accounting alternatives. The factors influencing an accountant have been listed which include the desires and demands of clients, economy of labor and the influence of income and tax regulations. The transition of an accounting student to an accounting practitioner, accounting examinations and alternative courses of action presented in accounting texts and the theoretical explanations to establish the conditions under which each method is applicable are described. The article stresses on the necessity of selecting a proper method due to a different substantial magnitude resulting from the various methods of matching cost with revenue. The statement made by the Committee on Accounting Procedure of the American Institute of Accountants in reference to inventory pricing has been quoted as an example of a practitioner's ability to express his opinion on the conformity of a client's financial statements. The article provides proof of the need for an authoritative guide of action under particular set of circumstances.